Impact of global catastrophes on online shoppers' behavior - Zhuk, Anton; Pavelko, Yevhen (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2024)
The article's subject matter is the impact of global catastrophes such as the COVID-19 pandemic and Russia's military aggression against Ukraine on consumer behavior in online stores, including changes in consumer purchasing habits and the adaptation of business marketing strategies. The work aims to develop methods for analyzing changes in consumer behavior in the face of global catastrophes and to develop recommendations for businesses to effectively respond to new market challenges. The following tasks were solved in the article: Investigating the impact of the COVID-19 pandemic and war in Ukraine on consumer behavior in online stores. Identifying key factors influencing consumer decisions during crises. Analyzing current marketing strategies and tools used by companies in crisis conditions. Developing recommendations for businesses to adapt to new realities and maintain competitiveness. The following methods are used: Mathematical data processing for analyzing survey results and statistical studies. Comparative analysis to compare consumer behavior before and during the pandemic. Expert assessments to determine the effectiveness of marketing strategies. Content analysis to study trends on social media and other online platforms. The following results were obtained – formulated principles for adapting marketing strategies in the context of the COVID-19 pandemic and wartime, identified that priorities for consumers include safety, health, availability of essential goods, and cybersecurity; changes in consumer behavior were identified, with consumers becoming more price-conscious and preferring products from local manufacturers; recommendations for businesses were developed regarding effective communication with customers, increased investments in online presence, ensuring convenience of feedback, enhancing emotional connection with customers, and offering flexible payment options; methods for supporting local businesses and optimizing resource utilization by consumers were proposed, emphasizing the importance of environmental responsibility and financial resource savings; a marketing study among the clients of the company "Gorgany" was conducted, which showed that the demand for outdoor recreation products remains high even during wartime, and that consumers prefer high-quality and affordable products from domestic manufacturers. Conclusions: the application of the method of analyzing changes in consumer behavior allowed to identify key factors influencing purchasing decisions in times of global crises, this gives businesses the opportunity to timely adapt their marketing strategies and maintain competitive advantages; the use of developed recommendations contributes to increasing business efficiency in times of pandemic and wartime, thanks to these recommendations, companies can better meet the needs of consumers, improve service quality, and increase customer loyalty; optimization of product range and improvement of digital presence are key success factors in the modern market, companies that quickly respond to changes in consumer priorities and use advanced technologies to communicate with customers have more chances for success.